Building Solidarity And Tolerance: Conflict Mitigation Through Religious Moderation Villages Assisted by Stakpn-Sentani in Entrop-Jayapura Subdistrict - Kabanga, Lewi; Malatuny, Yakob Godlif; Syafaat Siahaan, Daniel; N Pardomuan, Gusti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Conflict based on religion arose from a multicultural society, often triggered by simple issues and escalated into larger conflicts under the guise of religion. The objective of this community service was to build solidarity and tolerance in the District Entrop community in Jayapura City through the Moderate Religious Village activity initiated by STAKPN-Sentani. The method applied in this service went through several stages such as observation and interviews, Focus Group Discussions (FGD) as the core activity, declaration of the moderate village, and preparation of reports. The results of this activity included the formation of an understanding of mitigating religious conflict based on religious texts, where this mitigation involved an understanding of excerpts from the scriptures of each religion. Additionally, the culmination of the activity was the establishment of a moderated religious village under the guidance of STAKPN-Sentani in the Entrop Sub-district. Mitigating religious conflict in the Entrop Sub-district was closely linked to discourse within religious scriptures and the involvement of higher religious education due to the framework of the community's conditions.